Rectal Misoprostol in Women Undergoing Myomectomy for Intraoperative Blood Loss Reduction: A double-blinded randomized placebo-controlled study - Pruttaporn Maneerat; Sirikarn Tongmai (The Royal Thai College of Obstetricians and Gynaecologists, 2019)
Objectives: To compare amount of intraoperative blood loss between patients using preoperative rectal misoprostol versus placebo group.Materials and Methods: A randomized double-blinded placebo-controlled trial, 46 women with uterine leiomyoma indicated for myomectomy, both abdominal and laparoscopic approach were randomly assigned and received rectal misoprostol (400 μg) or placebo at 30 minutes before operation, then estimation of blood loss was recorded as primary outcome. Changes in hemoglobin, hematocrit, rate of transfusion and adverse events were also recorded.Results: Median and interquartile range of intraoperative blood loss in misoprostol group was 350 (613) ml and 500 (663) ml in placebo group. Mann-Whitney U test showed no statistical significance (p = 0.136). Univariate analyses showed significant factors of intraoperative blood loss were intramural type, type of operation and larger size of mass. But after multivariate analyses, the only significant factor affecting more blood loss was intramural type of leiomyoma (odds ratio 23, 95% confidence interval 1.96-271.9, p = 0.013). Changes of hemoglobin, hematocrit, transfusion rate and other complications were not significant.Conclusion: There was no significant benefit in blood loss reduction after using preoperative rectal misoprostol in the study.